2022
DOI: 10.1080/16549716.2022.2139340
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on incidence of surgery for acute type A aortic dissection in the Nordics

Abstract: We aimed to investigate a hypothesised association between daily mean temperature and the risk of surgery for acute type A aortic dissection (ATAAD). For the period of 1 January 2005 until 31 December 2019, we collected daily data on mean temperatures and date of 2995 operations for ATAAD at 10 Nordic cities included in the Nordic Consortium for Acute Type A Aortic Dissection (NORCAAD) collaboration. Using a two-stage time-series approach, we investigated the association between hot and cold temperatures relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The relation between varying acute illnesses and calendrical, geographical and meteorological phenomena has been investigated extensively lately. In addition to the current article, we have used the NORCAAD registry to investigate the relation between ATAAD and national holidays/weekends and temperature [ 2 , 3 ]. We observed that weekends and national holidays had a lower incidence of surgery for ATAAD and we found that cold (<−5°C) and warm (>21°C) temperatures seem to be associated with an increase in surgery for ATAAD.…”
mentioning
confidence: 99%
“…The relation between varying acute illnesses and calendrical, geographical and meteorological phenomena has been investigated extensively lately. In addition to the current article, we have used the NORCAAD registry to investigate the relation between ATAAD and national holidays/weekends and temperature [ 2 , 3 ]. We observed that weekends and national holidays had a lower incidence of surgery for ATAAD and we found that cold (<−5°C) and warm (>21°C) temperatures seem to be associated with an increase in surgery for ATAAD.…”
mentioning
confidence: 99%